Effectiveness and Efficiency Trade-Off in the Demerit Goods Taxation: a Non-Standard Approach - MUSOLINO, Francesco (Journal of Mathematical Economics and Finance, 2015)
The aim of this paper is to study a first approach to the trade-off relation between effectiveness and effi- ciency about the intervention of the State to protect merit goods, in presence of a constant consumer’s marginal utility. Moreover, we focus on how efficiency and effectiveness vary according to proportional and progressive taxes.